Student Professional Practice Management Information System At UIN Raden Fatah Palembang - Irfan Dwi Jaya; Mefta Eko Saputra; Ruliansyah Ruliansyah (Universitas Bina Darma, 2022)
Professional Practice (Internship) is one of the mandatory subjects in the Information Systems Study Program. Activities that occur during the implementation of the Professional Practice course are still conventional and not paperless. Moreover, there are several obstacles, such as students having difficulty finding a place for practical work because the study program does not yet have a list of companies that can do this activity. Moreover, it is also difficult for the Study Program to monitor whether students carry out activities appropriately. So that the Information Systems study program requires a Management Information System, which can assist the study program in carrying out practical work activities. The Management Information System built is web-based and uses the Waterfall method. From the research results, Management Information Systems assist students in registering and collecting reports; the study program makes it easier to assess and monitor students and makes document management easier.